NON FUNGIBLE TOKEN (NFT) SEBAGAI INSTRUMEN WAKAF DIGITAL: PELUANG DAN TANTANGAN DALAM PENGELOLAAN ASET SYARIAH - Ardiansyah, Jefri; Andriani Samsuri; Abu Yasid (CV. Denasya Smart Publisher, 2025)
Waqf is an Islamic economic instrument with significant potential to promote community welfare, yet it continues to face challenges related to transparency, asset certification, and public engagement. The advancement of blockchain technology particularly the use of Non-Fungible Tokens (NFTs) presents an innovative opportunity for the digitalization of waqf, especially as a means of creating unique, transparent, and verifiable asset certifications. This study employs a qualitative approach through a literature review to analyze the potential and challenges of utilizing NFTs within the framework of sharia-compliant digital waqf. The findings indicate that NFTs hold great promise in enhancing efficiency, expanding public participation, and promoting digitally-driven productive waqf models. However, several critical issues remain, including legal uncertainty, the risk of gharar (ambiguity), value volatility, and the lack of supporting infrastructure and digital literacy. This study recommends strengthening regulatory frameworks, developing adaptive fiqh guidelines, and increasing public education to support the implementation of NFTs as a waqf instrument aligned with maqāṣid al-sharī‘ah and capable of delivering broad benefits to the Muslim community.